The dynamic competitiveness of US agricultural and forest carbon sequestration - Heng-Chi Lee; Bruce A. McCarl (The University of Western Ontario, Department of Economics, 2003)
Global society is moving towards action to reduce anthropogenic greenhouse gas emissions. This can be expensive and socially disruptive in countries like the United States where the vast majority of emissions arise from electrical energy generation and petroleum usage. Agricultural and forest carbon sequestration along with development of other greenhouse gas offsets may help hold costs and disruption down. However sequestration exhibits saturation and non permanence that may influence this role. We examine the dynamic role that the agricultural and forest sectors can play in emissions offsets and mitigation. A 100 year modeling analysis, depicting U.S. agricultural and forest sectoral activities is applied to simulate agricultural and forestry potential mitigation response. The results reveal that agriculture and forestry can play an important role principally through cropland soil sequestration, afforestation and biofuel provision. However the importance of these strategies varies with price and time. At low carbon prices and in the near term agricultural soils are most important in the longer term and at high prices powerplant feedstock biofuels dominate. Ignoring saturation leads to an overstatement of the potential importance of sequestration strategies. Nevertheless the results show that the agricultural and forest sectors may serve as an important bridge to the future helping to hold costs down until energy emissions related technology develops.
Keywords: Q54; Q58; 330; climate change mitigation; saturation; carbon sequestration; Klimaschutz; Kohlendioxid; Landwirtschaft; Forstwirtschaft; Mathematische Optimierung; USA